A Hierarchical Taxonomy of Test Validity for More Flexibility of Validation - Chen, Jinsong (Frontiers in Psychology, 2018)
Test validity lies at the core of educational and psychological testing, but there are controversies about what test validity is and how test validation should proceed. This paper proposes a taxonomy to redefine test validity with hierarchical levels. On the basis of testing foundation, the hierarchy includes operational, measurable, realizable, and useful levels, which result in testing consequence. With the help of a context-specific construct, different levels of test validity, and different types of score use, the proposed taxonomy offers more flexibility for test validation. It can also shed light on the interpretations of important testing concepts and help streamline test development. Real-life examples are given to demonstrate the usefulness of the taxonomy across different settings.